Phenotypic plasticity in oysters (Crassostrea virginica) mediated by chemical signals from predators and injured prey. Issue 2 (30th April 2016) - Scherer, Avery E.; Lunt, Jessica; Draper, Alex M.; Smee, Delbert L.
Abstract: Prey organisms reduce predation risk by altering their behavior, morphology, or life history. Avoiding or deterring predators often incurs costs, such as reductions in growth or fecundity. Prey minimize costs by limiting predator avoidance or deterrence to situations that pose significant risk of injury or death, requiring them to gather information regarding the relative threat potential predators pose. Chemical cues are often used for risk evaluation, and we investigated morphological responses of oysters ( Crassostrea virginica ) to chemical cues from injured conspecifics, from heterospecifics, and from predatory blue crabs ( Callinectes sapidus ) reared on different diets. Previous studies found newly settled oysters reacted to crab predators by growing heavier, stronger shells, but that adult oysters did not. We exposed oysters at two size classes (newly settled oyster spat and juveniles 2.0 cm) to predation risk cue treatments including predator or injured prey exudates and to seawater controls. Since both of the size classes tested can be eaten by blue crabs, we hypothesized that both would react to crab exudates by producing heavier, stronger shells. Oyster spat grew heavier shells that required significantly more force to break, an effective measure against predatory crabs, when exposed to chemical exudates from blue crabs as compared to controls. When exposed to chemical cues from injured conspecifics or from injured clams ( Mercenaria mercenaria ), a sympatric bivalve, shell mass and force were intermediate between predator treatments and controls, indicating that oysters react to injured prey cues but not as strongly as to cues released by predators. Juvenile oysters of 2.0 cm did not significantly alter their shell morphology in any of the treatments. Thus, newly settled oysters can differentiate between predatory threats and adjust their responses accordingly, with the strongest responses being to exudates released by predators, but oysters of 2.0 cm and larger do not react morphologically to predatory threats.